Analisis Perbandingan Top 10 Best-Value dan Top 10 Traveler-Ranked Hotel di Kota Ternate Menggunakan MOORA - Yerik Afrianto Singgalen (Journal of Computer System and Informatics (JoSYC), 2023)
There are a variety of factors that influence hotel visitors' decisions. The first consideration pertains to the room and amenities, while the second comprises prior guest ratings. Tripadvisor is frequently used to propose lodging and amenity services in different places. Using the MOORA decision support model, this study compares the top 10 best-value hotels in Ternate City to the top 10 most-recommended hotels by travelers. This research consists of four phases: the data gathering phase, the data analysis phase, the data interpretation phase, and the reporting phase. The data processing results utilizing the MOORA decision support model on the top 10 best-value hotels in Ternate City revealed a considerable disparity with the Tripadvisor rankings based on room and amenity criteria and guest reviews. Muara Hotel Ternate has a total scale of 0.491% based on parameters related to its rooms and amenities. Additionally, the order is dynamic and dependent on guest rating criteria. The Bela International Hotel ranks #1 if review data is considered because its reviews exceed 100. The same conclusion was drawn from the data processing findings of the top 10 traveler-ranked hotels in Ternate City, where the ranking results based on room and amenities criteria refer to the Ternate City Hotel with a total yi value of 0.79. The ranking results are also dynamic and dependent on guest rating criteria. If the number of reviews is considered, the Bela International Hotel will be ranked #1 because its number of studies is more significant than 100. This implies that information about rooms and hotel amenities and the number of guest evaluations on the Tripadvisor website can be crucial in influencing hotel guests' decisions regarding their stay.